The Ethnogeomorphological Vision of Artisan Fishermen from the Community of Guriú, Camocim-Ceará (Global Journal of Human-Social Science, 2024)
Ethnogeomorphology which is the understanding of relief through the knowledge of traditional communities has been increasingly required within geographic science when the approach takes into account man s dialectical action on his environment In the search for an understanding of coastal ethnogeomorphology we chose to research the coast of Cear which among its morphological features contains river mouths fixed and mobile dunes cliffs lake environments fluviomarine plains and all interconnected in an interaction of landscape dynamics All the compartmentalizations expressed in the relief make the coastal landscape a space of great natural expressiveness within the space of Cear Added to these is anthropic action forming geographic space the object of study in Geography which is formed by the dialectical interaction between man and the space that surrounds him The present work is the result of qualitative research carried out on Guri beach located in the municipality of Camocim-Cear This work aims to survey the traditional knowledge of artisanal fishing workers in the Guri district about the local relief and the way they interact with the environment The research methodology was divided into bibliographic and cartographic survey field research semistructured interview and data analysis
Keywords: ethnogeomorphology; landscape and traditional communities